Glaucoma-related adverse events in the first five years after unilateral cataract removal in the Infant Aphakia Treatment Study - Freedman, Sharon F. (JAMA Ophthalmol, 2015)
IMPORTANCE: Glaucoma-related adverse events constitute major sight-threatening complications of cataract removal in infancy, yet their relationship to aphakia versus primary intraocular lens (IOL) implantation remains unsettled. OBJECTIVE: To identify and characterize cases of glaucoma and glaucoma-related adverse events (glaucoma+glaucoma suspect) among children in the Infant Aphakia Treatment Study (IATS) by the age of five years. DESIGN, SETTING, AND PARTICIPANTS: A multicenter randomized controlled trial of 114 infants with unilateral congenital cataract who were between age 1–6 months at surgery. INTERVENTIONS: Participants were randomized at cataract surgery to either primary IOL, or no IOL implantation (contact lens [CL]). Standardized definitions of glaucoma and glaucoma suspect were created for IATS and applied for surveillance and diagnosis. MAIN OUTCOME MEASURES: Development of glaucoma and glaucoma+glaucoma suspect in operated eyes up to age five years, plus intraocular pressure, visual acuity, and axial length at age five years. RESULTS: Product limit estimates of the risk of glaucoma and glaucoma+glaucoma suspect at 4.8 years after surgery were 17% (95%CI=11%–25%) and 31% (95%CI=24%–41%), respectively. The CL and IOL groups were not significantly different for either outcome: glaucoma (hazard ratio(HR)=0.8[95%CI=0.3–2.0],p=0.62); glaucoma+glaucoma suspect: (HR=1.3[95%CI=0.6–2.5],p=0.58). Younger (versus older) age at surgery conferred increased risk of glaucoma (26% versus 9%, respectively at 4.8 years after surgery (HR=3.2[95%CI=1.2–8.3]), and smaller (versus larger) corneal diameter showed increased risk for glaucoma+glaucoma suspect (HR=2.5[95%CI=1.3–5.0]). Age and corneal diameter were significantly positively correlated. Glaucoma was predominantly open angle (19/20 cases, 95%), most eyes received medication (19/20, 95%), and 8/20 (40%) eyes had surgery. CONCLUSIONS AND RELEVANCE: These results suggest that glaucoma-related adverse events are common and increase between one and five years in infants after unilateral cataract removal at 1–6 months of age; primary IOL placement does not mitigate their risk, but surgery at a younger age increases the risk. Longer follow-up of these children may further characterize risk factors, long-term outcomes, potential differences between eyes having primary IOL vs. aphakia, and optimal timing of unilateral congenital cataract removal.